1872 Cleveland Gen. Ordinances 102, An Ordinance to Prevent the Careless Use of Fire-Arms, § 1 - (:unkn) unknown (My University, 1872)
That any person who shall intentionally, without malice, point or aim any fire-arm at or toward any other person, shall be subject to a fine of not less than five dollars, nor more than fifty dollars.
Keywords: BRANDISHING